Potentiating angiogenesis arrest in vivo via laser irradiation of peptide functionalised gold nanoparticles - Pedro Pedrosa; Amelie Heuer-Jungemann; Antonios G. Kanaras; Alexandra R. Fernandes; Pedro V. Baptista (Journal of Nanobiotechnology, 2017)
Abstract Background Anti-angiogenic therapy has great potential for cancer therapy with several FDA approved formulations but there are considerable side effects upon the normal blood vessels that decrease the potential application of such therapeutics. Chicken chorioallantoic membrane (CAM) has been used as a model to study angiogenesis in vivo. Using a CAM model, it had been previously shown that spherical gold nanoparticles functionalised with an anti-angiogenic peptide can humper neo-angiogenesis. Results Our results show that gold nanoparticles conjugated with an anti-angiogenic peptide can be combined with visible laser irradiation to enhance angiogenesis arrest in vivo. We show that a green laser coupled to gold nanoparticles can achieve high localized temperatures able to precisely cauterize blood vessels. This combined therapy acts via VEGFR pathway inhibition, leading to a fourfold reduction in FLT-1 expression. Conclusions The proposed phototherapy extends the use of visible lasers in clinics, combining it with chemotherapy to potentiate cancer treatment. This approach allows the reduction of dose of anti-angiogenic peptide, thus reducing possible side effects, while destroying blood vessels supply critical for tumour progression.